TERDAFTARNYA KATA UMUM "AJAIB" SEBAGAI MEREK PADA DAFTAR UMUM MEREK - Shafa Bakadam; Rr. Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2021)
In the Intellectual Property Database, four words "Magic" were found which were used as trademarks with registered status. Article 20 letter f of Law Number 20 of 2016 concerning Marks and Geographical Indications states that a mark cannot be registered if it is a public name and/or a symbol of public property. The main problem is whether the word Magic is not included in the category of common words so that its registration is accepted and what are the legal consequences for the acceptance of registration of common words as a mark and what legal remedies can be taken based on Law Number 20 of 2016 concerning Marks and Geographical Indications. The research was conducted using normative legal research methods, with secondary data supported by primary data. The nature of the research is descriptive and conclusions are drawn using the deductive method. Based on the research results, the word Magic is a general word, so registration as a trademark cannot be accepted.